US and the Middle East : PR fiasco looms for Obama - Dorsey, James M. (2012)
President Obama faces a public relations disaster in the Arab and Muslim world next month with his expected rejection of recognition of Palestinian statehood by the United Nations General Assembly. Obama could do much to restore his country's image and reaffirm the US as a player despite its unpopular policies.